Reduced laser‐evoked potential habituation detects abnormal central pain processing in painful radiculopathy patients. (20th January 2017) - Hüllemann, P.; von der Brelie, C.; Manthey, G.; Düsterhöft, J.; Helmers, A.K.; Synowitz, M.; Baron, R.
Abstract: Background: Repetitive painful laser stimuli lead to physiological laser‐evoked potential (LEP) habituation, measurable by a decrement of the N2/P2 amplitude. The time course of LEP‐habituation is reduced in the capsaicin model for peripheral and central sensitization and in patients with migraine and fibromyalgia. In the present investigation, we aimed to assess the time course of LEP‐habituation in a neuropathic pain syndrome, i.e. painful radiculopathy. Methods: At the side of radiating pain, four blocks of 25 painful laser stimuli each were applied to the ventral thigh at the L3 dermatome in 27 patients with painful radiculopathy. Inclusion criteria were (1) at least one neurological finding of radiculopathy, (2) low back pain with radiation into the foot and (3) a positive one‐sided compression of the L5 and/or S1 root in the MRI. The time course of LEP‐habituation was compared to 20 healthy height and age matched controls. Signs of peripheral (heat hyperalgesia) and central sensitization (dynamic mechanical allodynia and hyperalgesia) at the affected L5 or S1 dermatome were assessed with quantitative sensory testing. Results: Painful radiculopathy patients showed decreased LEP‐habituation compared to controls. Patients with signs of central sensitization showed a more prominent LEP‐habituation decrease within the radiculopathy patient group. Conclusions: Laser‐evoked potential habituation is reduced in painful radiculopathy patients, which indicates an abnormal central pain processing. Central sensitization seems to be a major contributor to abnormal LEP habituation. The LEP habituation paradigm might be useful as a clinical tool to assess central pain processing alterations in nociceptive and neuropathic pain conditions. Significance: Abnormal central pain processing in neuropathic pain conditions may be revealed with the laser‐evoked potential habituation paradigm. In painful radiculopathy patients, LEP‐habituation is reduced compared to healthy controls.